Análise da vegetação em um fragmento de caatinga no município de Porto da Folha, Sergipe, Brasil - Oliveira, Diogo Gallo de (2012)
This research was conducted in a fragment of Caatinga with around 50 ha in São Pedro farm, located at Porto da Folha City, Sergipe, order to know the floristic composition and phytossociological structure of herbaceous and shrub-tree components, verify the relationships physiognomic of the shrub-tree with other Caatinga areas, as well as the existence of edge effect in the fragment studied, with the intention of generate subsidies to studies of ecology, conservation and recovery of degraded areas in the region. Thus, it was tested the following null hypotheses: 1st - there is no difference in the structure and richness of shrub-tree of fragment studied in comparison with other areas of Caatinga analyzed in Sergipe and in the Northeast; 2nd - there is no difference in the floristic composition and phytossociological structure of herbaceous vegetation between two seasons (dry and wet); 3rd - there is no difference in the floristic composition and structure of the shrub-tree between edge and interior of the fragment Caatinga studied. For testing the first hypothesis, it was conducted sampling of shrub- tree through of 25 plots, with 20x20m (400m²), distributed systematically at intervals of 141 m in two directions perpendicular to each plot. All individuals of shrubs-trees were identified and recorded with at breast height circumference (BHC at 1.30 m from ground level) ≥ 6.0 cm and analyzed the floristic composition, the phytossociological structure (density, frequency, dominance and importance value), diversity in addition to spatial distribution and floristic similarity. Species richness and structural parameters of the component of shrubs-trees found in the fragment studied was higher than in most surveys in other areas of Caatinga dominium, considering the different types analyzed ( Caatinga Caducifólia Espinhosa , Caatinga Caducifólia Não Espinhosa and Vegetação Estacional Decidual ). The vegetation that was in the fragment studied can be classified as Caatinga Caducifólia Espinhosa (Caatinga sensu stricto) showed the highest similarity to other semiarid areas that have this same type of plant formation. For testing the second hypothesis, two samples were realized of the herbaceous component for comparison, in the rainy season and one during the dry season on 25 smaller plots with 1x1 m (1m ²) distributed systematically within plots of 20x20m, a distance of 10 meters, following is the angle of 45° from the first vertex of each plot. All living plants were measured and identified with stem/pseudo-stem chlorophyll with absence or low level of lignifications that were not seedlings of woody species and analyzed the floristic composition, the phytossociological structure (density, frequency, dominance and importance value), diversity in addition to life forms of Raunkiaer. The density, frequency, dominance and importance value of herbaceous populations, as well as height and diameter of plants were low in the dry season. The diversity of herbaceous species recorded for the fragment was more than most of the studies that was done in other areas of Caatinga of Northeast Brazil, which can be associated to good state of conservation of the studied fragment. The life-form predominant of vegetation was the therophytes, followed by phanerophytes, featuring a therophytic phytoclimate to the region of the study area. The analysis of structural patterns and diversity conducted only in two distinct seasons are not enough to know, in detail, the ecological dynamics of the herbaceous component of caatinga in the fragment studied. For test the third hypothesis were selected 24 permanent plots with 20x20 m, being 12 marked in the edge and 12 inside the fragment, in a systematic manner, at intervals of 141 m. In each plot were identified and recorded all individuals of shrubs and trees with at breast height circumference (BHC at 1.30 m from xii ground level) ≥ 6.0 cm and measured variables dendrometric for the calculations of diversity and structure, addition to these variables was calculated leaf area index using hemispherical photos with the lens "fisheye" 180 ° in the center of each plot. We used non-metric multidimensional scaling (NMDS) to check whether there are differences in species composition between plots of the edge and interior. To determine the floristic similarity between plots evaluated in different environments, we used the similarity analysis (ANOSIM). Differences between the sampled environmental variables (dependent variables) in relation to the location of the edge and interior plots (independent variable) were tested using generalized linear models (GLM's). The plots of edge presented 43 species and 1157 individuals, while the interior of the 1377 individuals and 42 species. The NMDS ordination showed that there are not clear differences in species composition between the two environments analyzed (edge and interior). The five structural parameters vegetation analyzed between plots located the edges and interior the fragment (tree height, stem diameter, basal area, number of individuals and leaf area index) did not result in statistically significant differences. In relation to the richness, diversity species and evenness indexes was verified also that there is no statistically significant difference between the environment the edge and interior. The physiognomic and structural similarities of vegetation in the study area, evidenced by the richness, abundance and distribution of species in different locations (edge and interior), suggest the existence of a common pattern, possibly related to the availability of resources in an equitable manner (as light, water and nutrients), history of conservation of the vegetation of the fragment, as well as the heterogeneity and complexity of the environmental area. Indicating that the community arbustivo-arboreal of the fragment of Caatinga studied is not ecologically affected by the presence of the edges.